Iron phosphate material and preparation method thereof, positive electrode material, positive electrode plate and secondary battery

By using small-sized iron phosphate particle materials with ring-like structures and adopting specific preparation methods, the problem of high energy consumption during preparation of lithium iron phosphate materials in the prior art is solved, and a more efficient nanoification process and better electrochemical performance are achieved.

CN119695144APending Publication Date: 2025-03-25HUBEI HONGRUN HIGH-TECH NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411721854.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, when preparing lithium iron phosphate materials, a large amount of energy is required to sand the iron phosphate particles to the nanoscale, resulting in large energy consumption.

Method used

A small-sized iron phosphate particle material with a ring structure and a D50 particle size less than 1 μm is used as the precursor. A specific preparation method, such as controlling the pH value and temperature of the iron-phosphorus solution, adding an oxidant and subjecting high-temperature boiling treatment to form a complex of iron-phosphate-hydrochloric acid. Finally, a nano-scale iron phosphate material was obtained by dilution-cold excitation decomplexing.

Benefits of technology

The energy consumption required for nanoification is reduced, and iron phosphate materials with smaller particle sizes are obtained, thereby improving the conductive properties of lithium iron phosphate materials, reducing the energy consumption and cost of preparation of positive electrode sheets and secondary batteries, and improving electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695144A_ABST
    Figure CN119695144A_ABST
Patent Text Reader

Abstract

The invention provides an iron phosphate material and a preparation method thereof, a positive electrode material, a positive electrode plate and a secondary battery, and belongs to the technical field of nanomaterials, the iron phosphate material comprises iron phosphate particles, the iron phosphate particles have an annular structure, and the D50 particle size of the iron phosphate particles is less than 1 [mu] m. When the iron phosphate material is used as a precursor to prepare lithium iron phosphate, the energy consumption of a sanding process can be effectively reduced, and the process efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of inorganic materials, and in particular to an iron phosphate material and a preparation method thereof, a positive electrode material, a positive electrode sheet and a secondary battery. Background Art

[0002] Ferric phosphate is an off-white or off-white powder. It can form a variety of hydrates, including dihydrated ferric phosphate, tetrahydrated ferric phosphate and octahydrated ferric phosphate. Usually, dihydrated ferric phosphate (relative molecular weight: 186.82) is generated, and it starts to lose crystal water when heated to about 160°C. Ferric phosphate has a rich skeleton structure, unique ion exchange properties and electrochemical properties. It is an excellent material for preparing lithium iron phosphate, a positive electrode material for lithium-ion batteries that is widely used in new energy fields (such as new energy vehicles).

[0003] In the prior art, the conductivity of lithium iron phosphate is improved by nano-crystallizing the key raw material for synthesizing lithium iron phosphate or lithium iron manganese phosphate. At present, the D50 particle size of iron phosphate prepared by conventional processes is usually between 2μm and 30μm. Therefore, when preparing lithium iron phosphate or lithium iron manganese phosphate with the expected conductivity, a large amount of energy is required to grind the iron phosphate particles to the nanoscale, which consumes a lot of energy. Summary of the invention

[0004] In view of the technical problems existing in the background technology, the present application provides an iron phosphate material and a preparation method thereof, a positive electrode material, a positive electrode plate and a secondary battery. The iron phosphate material provided by the present application is easier to obtain nano-scale iron phosphate material, reduces the energy consumption required for nano-ization and is easier to obtain iron phosphate materials with smaller particle sizes, thereby making it easier to improve the conductivity of the prepared lithium iron phosphate material.

[0005] In a first aspect, an embodiment of the present application provides an iron phosphate material, the iron phosphate material includes iron phosphate particles, the iron phosphate particles have a ring structure, and the D50 particle size of the iron phosphate particles is less than 1 μm.

[0006] In the technical solution of the embodiment of the present application, the iron phosphate material adopts a small-sized iron phosphate particle material with a ring structure and a D50 particle size of less than 1 μm. When used as a precursor to prepare lithium iron phosphate, it is beneficial to reduce the energy consumption required for nano-sizing and make it easier to obtain iron phosphate materials with smaller particle sizes, thereby making it easier to improve the conductivity of the prepared lithium iron phosphate material.

[0007] In some embodiments, the aggregation index of the particle size of the iron phosphate particles satisfies: 0.5≤(D90-D10) / D50≤2.

[0008] In this embodiment, the particle size distribution of the iron phosphate particles is more concentrated, which is beneficial to improving the grinding efficiency and obtaining nano-scale iron phosphate particles with uniform size by sand grinding, so that in the subsequent lithium iron phosphate preparation process, lithium ions are evenly distributed in the iron phosphate particles, and lithium iron phosphate materials with high conductivity and excellent electrochemical properties are obtained.

[0009] In some embodiments, the ratio of the average inner diameter to the average outer diameter of the ring structure of the iron phosphate particles is (0.35-0.48):1.

[0010] In this embodiment, in the technical scheme of the embodiment of the present application, the ring diameter (the distance between the outer diameter and the inner diameter of the ring) affects the grinding efficiency and the morphology of the grinding particles. A ring diameter that is too large is not conducive to improving the grinding efficiency, and a ring diameter that is too small is prone to irregular fractures during the grinding process. Iron phosphate particles within the above-mentioned size range are conducive to improving the grinding efficiency and obtaining small nano-scale iron phosphate particles with regular morphology and uniform size, so that lithium ions are evenly distributed in the iron phosphate particles in the subsequent lithium iron phosphate preparation process.

[0011] In some embodiments, the average inner diameter of the ring structure of the iron phosphate particles ranges from 178 nm to 559 nm, and the average outer diameter of the ring structure of the iron phosphate particles ranges from 474.60 nm to 1188.90 nm.

[0012] In the above embodiment, the iron phosphate particles within the above size range are conducive to improving the grinding efficiency and obtaining nano-scale iron phosphate particles with regular morphology and uniform size.

[0013] In some embodiments, the specific surface area of ​​the iron phosphate particles is 13 m 2 / g~20m 2 / g.

[0014] In this embodiment, during the preparation of lithium iron phosphate, the larger specific surface area of ​​the iron phosphate particles is conducive to the uniform distribution of lithium ions in the iron phosphate material, and can increase the contact area between the iron phosphate materials, promote the bonding between the iron phosphate materials, thereby improving the overall conductivity and cycle stability of the prepared lithium iron phosphate material. The present application controls the specific surface area of ​​the iron phosphate material to be within the above range, which is conducive to grinding to obtain nano-scale iron phosphate particles with a high specific surface area, thereby preparing a lithium iron phosphate material with high conductivity and high cycle performance.

[0015] In a second aspect, the present application provides a method for preparing an iron phosphate material, comprising the following steps:

[0016] preparing an iron-phosphorus solution comprising a ferrous ion source, a chloride ion source, and a phosphate ion source, wherein the pH value of the iron-phosphorus solution is not greater than 1.5;

[0017] The iron-phosphorus solution is heated to above 70° C., and then an oxidant is added to the iron-phosphorus solution to obtain an iron phosphate slurry;

[0018] The ferric phosphate slurry is heated to boiling, and after the ferric phosphate slurry changes color, the boiling state is maintained for 1.5 hours to 4 hours to obtain a first slurry;

[0019] Mixing the first slurry with low-temperature dilution water to obtain a second slurry;

[0020] The second slurry is subjected to solid-liquid separation to obtain an iron phosphate material.

[0021] In the technical scheme of the embodiment of the present application, a chloride ion system is used to prepare an iron phosphate material. The pH value of the iron-phosphorus solution is controlled to inhibit the hydrolysis of ferrous ions and reduce the agglomeration of subsequently generated ferric phosphate ions. The temperature of the iron-phosphorus solution is controlled and the ferrous ions are oxidized to obtain an iron phosphate-containing slurry. The iron phosphate slurry is then heated to boiling, and the volatility and complexing properties of hydrogen chloride are used to form an iron phosphate-hydrochloric acid complex with the iron phosphate particles in the iron phosphate slurry. Low-temperature dilution water is then added to the first slurry, and the iron phosphate particles with a D50 particle size of less than 1 μm and a ring structure are finally prepared through dilution-cold excitation decomposition and complexation, so that nano-scale iron phosphate materials are easier to obtain. When the iron phosphate material is used as a precursor to prepare lithium iron phosphate, it is beneficial to reduce the energy consumption required for nano-sizing and it is easier to obtain iron phosphate materials with smaller particle sizes, thereby making it easier to improve the conductivity of the prepared lithium iron phosphate material.

[0022] In some embodiments, the molar ratio of the iron element, the phosphorus element, and the chlorine element in the iron-phosphorus solution is (0.8-1.2):(0.8-2):(0.5-3).

[0023] In the above embodiments, the iron, phosphorus and chlorine elements in the reaction system affect the yield, size and morphology of the generated iron phosphate particles. For example, a higher iron-chlorine ratio and phosphorus-chlorine ratio are conducive to the precipitation of iron phosphate to obtain a higher iron phosphate yield. A smaller phosphorus-chlorine ratio is conducive to the formation of an iron phosphate-hydrochloric acid complex in the high-temperature boiling stage, reducing the agglomeration of iron phosphate to obtain an iron phosphate material with a smaller size and good dispersion. By controlling the iron, phosphorus and chlorine elements to be within the above ratios, an iron phosphate material with a ring structure and a D50 particle size of less than 1 μm can be obtained with a higher yield.

[0024] In some embodiments, the molar ratio of the iron element, the phosphorus element, and the chlorine element in the iron-phosphorus solution is 1:(1-1.2):(2-3).

[0025] In the above embodiment, controlling the iron element, phosphorus element and chlorine element to be within the above range is conducive to sufficient precipitation of the iron element to form iron phosphate to obtain a higher yield, and the obtained iron phosphate material has a regular morphology and good particle dispersion.

[0026] In some embodiments, the oxidant is selected from an aqueous solution of hydrogen peroxide, the molar ratio of hydrogen peroxide in the aqueous solution of hydrogen peroxide to the iron element in the iron-phosphorus solution is (0.6-1):1, and the concentration of the iron element in the iron-phosphorus solution is 0.5 mol / L-2.0 mol / L.

[0027] In the above embodiment, the ratio of hydrogen peroxide to the iron element in the iron-phosphorus solution and the concentration of the iron element affect the oxidation rate of ferrous ions, thereby affecting the rate of formation of crystal nuclei of iron phosphate and the growth rate of crystals. Under the above conditions, it is beneficial to obtain an iron phosphate slurry with smaller iron phosphate particles, to generate more iron phosphate-hydrochloric acid complexes in the subsequent high-temperature boiling stage, and to stably and evenly disperse the iron phosphate-hydrochloric acid complexes in the first slurry, thereby reducing the agglomeration of iron phosphate particles, thereby generating small-sized iron phosphate materials with good particle dispersion in the subsequent dilution-cold excitation decomposition complexation stage.

[0028] In some embodiments, the aqueous solution of hydrogen peroxide is added to the iron-phosphorus solution by dropwise addition, and the dropwise addition time is 5 min to 15 min. After the dropwise addition is completed, the solution is stirred for 5 min to 15 min to obtain an iron phosphate slurry.

[0029] In the above embodiment, the hydrogen peroxide dripping acceleration and stirring time affect the formation of iron phosphate nuclei and the growth of crystals. Under the above conditions, it is beneficial to quickly generate iron phosphate nuclei and inhibit crystal growth, thereby obtaining an iron phosphate slurry with smaller iron phosphate particles, so that more iron phosphate-hydrochloric acid complexes can be generated in the subsequent high-temperature boiling stage, and it is beneficial for the iron phosphate-hydrochloric acid complexes to be stably and evenly dispersed in the first slurry, reducing the agglomeration of iron phosphate particles, thereby generating small-sized iron phosphate materials with good particle dispersion in the subsequent dilution-cold excitation decomposition complexation stage.

[0030] In some embodiments, the steps of heating the iron-phosphorus solution to above 70° C. and then adding an oxidant to the iron-phosphorus solution to obtain the iron phosphate slurry include:

[0031] The iron-phosphorus solution is heated to 70° C. to 80° C., and then an aqueous solution of hydrogen peroxide is added to the iron-phosphorus solution.

[0032] In the above embodiment, an aqueous solution of hydrogen peroxide is used and the temperature of the iron-phosphorus solution is controlled at 70°C to 80°C, which is conducive to the full reaction of hydrogen peroxide with the iron-phosphorus solution, improves the oxidation efficiency of ferrous ions, and facilitates the rapid generation of a large number of small-sized iron phosphate particles at this stage, which is conducive to the subsequent high-temperature boiling stage to generate more iron phosphate-hydrochloric acid complexes, and is conducive to the stable and uniform dispersion of the iron phosphate-hydrochloric acid complexes in the first slurry, thereby preparing a small-sized iron phosphate material with good particle dispersibility.

[0033] In some embodiments, the mass fraction of hydrogen peroxide in the aqueous solution of hydrogen peroxide is 20% to 30%.

[0034] In the above embodiment, the hydrogen peroxide is within the above content, which is convenient for quickly generating iron phosphate particles and can effectively reduce the decomposition loss of hydrogen peroxide itself during the oxidation process of ferrous ions.

[0035] In some embodiments, the ferrous ion source is selected from one or more of ferrous nitrate and ferrous chloride.

[0036] In the above embodiments, the above ferrous ion sources can provide the necessary ferrous ions for the iron-phosphorus solution reaction system. When ferrous nitrate is used as the ferrous salt, the free nitrate ions in the system can form nitric acid and be volatilized and removed during the subsequent boiling process. When ferrous chloride is used as the ferrous salt, the free chloride ions in the system can be volatilized and removed in the form of hydrochloric acid during the subsequent boiling process, so as to reduce the acidity of the system and impurities, and facilitate the subsequent acquisition of small-sized and high-yield iron phosphate.

[0037] In some embodiments, the source of ferrous ions is selected from ferrous chloride.

[0038] In the above embodiment, ferrous chloride introduces chloride ions while providing ferrous ions, so as to subsequently complex with iron phosphate particles to form an iron phosphate-hydrochloric acid complex, thereby reducing the aggregation of iron phosphate and avoiding the introduction of impurities such as nitrogen and oxygen.

[0039] In some embodiments, the chloride ion source is selected from at least one of hydrochloric acid and ferrous chloride.

[0040] In the above embodiments, hydrochloric acid and ferrous chloride can both provide chloride ions required for the reaction and reduce the introduction of other impurity cations.

[0041] In some embodiments, the phosphate ion source is selected from H 3 PO 4 NH 4 )H 2 PO 4 NH 4 ) 2 HPO 4 At least one of .

[0042] In the above embodiment, H 3 PO 4 NH 4 )H 2 PO 4 NH 4 ) 2 HPO 4 It can provide the phosphate ions required for the reaction.

[0043] In some embodiments, the steps for preparing the iron-phosphorus solution are as follows:

[0044] A ferrous ion source, a chloride ion source, a phosphate ion source and water are mixed and the pH value is controlled to be no greater than 1.5 to obtain an iron-phosphorus solution.

[0045] In some embodiments, the desired iron-phosphorus solution can be obtained by directly mixing a ferrous ion source, a chloride ion source, a phosphate ion source and water, and the process is simple.

[0046] In some embodiments, the ferrous ion source is ferrous chloride, the chloride ion source is selected from ferrous chloride and hydrochloric acid, and the phosphate ion source is phosphoric acid.

[0047] In the above embodiment, ferrous chloride is used as both a ferrous ion source and a chloride ion source, hydrochloric acid is used as a chloride ion source and provides acidity conditions for the reaction, and phosphate is used as a phosphorus source and can provide acidity conditions for the reaction. The pH value of the system and the ratio of ferrous ions, phosphate ions, and chloride ions can be controlled by the ratio of the above raw materials. No additional acid or alkali (such as sulfuric acid, nitric acid, sodium hydroxide, ammonia water, etc.) is required. While preparing an iron phosphate material with a ring structure and a smaller size, the impurity ions (such as sulfate, nitrate, sodium ion, NH4+) can be minimized. 4 + The high-purity iron phosphate material is prepared by the introduction of the iron phosphate material, thereby improving the cycle life and capacity retention rate of the lithium iron phosphate prepared with the iron phosphate material as the raw material when used in the battery.

[0048] In some embodiments, the steps for preparing the iron-phosphorus solution are as follows:

[0049] Heat the dilute hydrochloric acid aqueous solution to 50°C to 70°C, then add the elemental iron material to react to obtain a ferrous chloride solution, wherein the concentration of the dilute hydrochloric acid aqueous solution is 1.0 mol / L to 4.0 mol / L;

[0050] Phosphoric acid and water are added to the ferrous chloride solution, mixed and the pH value is controlled to be no greater than 1.5 to obtain an iron-phosphorus solution.

[0051] In the above embodiment, the iron-phosphorus solution is prepared using elemental iron material, hydrochloric acid aqueous solution and phosphoric acid as raw materials, which can minimize the introduction of impurity ions and prepare high-purity iron phosphate material.

[0052] In some embodiments, the elemental iron material is selected from one or more of iron sheets, iron powder, and iron blocks.

[0053] In some embodiments, the pH value of the iron-phosphorus solution is 0.2-1.5.

[0054] In the above embodiments, the pH value of the iron-phosphorus solution affects the generation rate and yield of iron phosphate. A higher pH value easily causes a large number of iron phosphate particles to agglomerate during the oxidation stage, while a lower pH value is not conducive to the precipitation of iron phosphate. Within the above pH value range, it is more conducive to obtaining high-yield and smaller-sized iron phosphate materials.

[0055] In some embodiments, the temperature difference between the second slurry and the first slurry is no less than 60°C.

[0056] In the above embodiment, the higher temperature difference is more conducive to the iron phosphate-hydrochloric acid decomplexation and cold quenching refinement, thereby generating iron phosphate materials with smaller sizes.

[0057] In some embodiments, the temperature difference between the second slurry and the first slurry is 70°C to 90°C.

[0058] In the above embodiment, controlling the temperature difference between the second slurry and the first slurry within the temperature range is more conducive to obtaining smaller-sized iron phosphate materials and obtaining a higher yield.

[0059] In some embodiments, the mass ratio of the first slurry to the low-temperature dilution water is 1:(10-20).

[0060] In the above embodiment, low-temperature dilution water is used to quickly cool down and dilute the system, which is beneficial to the decomplexation of the iron phosphate-hydrochloric acid complex to generate iron phosphate material. The mass ratio of the first slurry to the low-temperature dilution water is within the above range, which is beneficial to the rapid and complete decomplexation of the iron phosphate-hydrochloric acid complex, thereby obtaining a small-sized iron phosphate material with higher purity and higher yield.

[0061] In some embodiments, the first slurry is mixed with low-temperature dilution water and stirred until it changes color to obtain a second slurry.

[0062] In the above embodiment, during the high-temperature boiling treatment, an iron phosphate-hydrochloric acid complex is generated. After adding low-temperature dilution water and mixing, the iron phosphate is decomplexed and precipitated, and the color of the slurry changes.

[0063] In some embodiments, the second slurry is subjected to solid-liquid separation, and the obtained solid is washed and dried at 90° C. to 120° C. to obtain the iron phosphate material.

[0064] In the above embodiments, water can be quickly removed under the above conditions to obtain the iron phosphate material.

[0065] In a third aspect, an embodiment of the present application provides a positive electrode material, including at least one of a lithium iron phosphate material and a lithium iron manganese phosphate material. The lithium iron phosphate material is prepared from the above iron phosphate material or from an iron phosphate material prepared by the above method for preparing the iron phosphate material. The lithium iron manganese phosphate material is prepared from the above iron phosphate material or from an iron phosphate material prepared by the above method for preparing the iron phosphate material.

[0066] In a fourth aspect, an embodiment of the present application provides a positive electrode plate, which includes the above-mentioned positive electrode material.

[0067] In this embodiment, the positive electrode plate contains the above-mentioned positive electrode material, thereby having the advantages of reducing the energy consumption and cost of preparing the positive electrode plate and improving the conductive performance of the positive electrode plate.

[0068] In a fifth aspect, an embodiment of the present application provides a secondary battery, wherein the electrode sheet used for the positive electrode is the above-mentioned positive electrode electrode sheet.

[0069] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, which has the advantages of reducing the energy consumption and cost of secondary battery preparation and improving the electrochemical performance of the secondary battery.

[0070] In a sixth aspect, an embodiment of the present application provides an electrical device, comprising the above-mentioned secondary battery.

[0071] In this embodiment, the electric device includes the secondary battery, which has the advantages of reducing the energy consumption and cost of preparing the electric device and improving the electrochemical performance of the electric device.

[0072] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0074] Figure 1 This is a scanning electron microscope (SEM) test result diagram of the iron phosphate material prepared in Example 1;

[0075] Figure 2 This is a SEM test result diagram of the iron phosphate material prepared in Example 1;

[0076] Figure 3 This is a flow chart of the steps of the method for preparing the iron phosphate material of an embodiment of the present application;

[0077] Figure 4 This is an X-ray diffraction (XRD) test result diagram of the iron phosphate material prepared in Example 1, wherein the abscissa is the diffraction angle Two-Theta (°), and the ordinate is the diffraction intensity Intensity (Counts);

[0078] Figure 5 This is a SEM test result diagram of the iron phosphate material prepared in Comparative Example 6;

[0079] Figure 6 This is a SEM test result diagram of the iron phosphate material prepared in Comparative Example 6;

[0080] Figure 7 This is a graph of the XRD test results of the iron phosphate material prepared in Comparative Example 6, wherein the abscissa is the diffraction angle Two-Theta (°), and the ordinate is the diffraction intensity Intensity (Counts). DETAILED DESCRIPTION

[0081] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0082] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0083] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0084] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0085] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0086] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0087] In the embodiments of the present application, unless otherwise specified, water can be at least one of distilled water, deionized water, pure water, and ultrapure water; the solvent used in the "solution" or "aqueous solution" is selected from at least one of distilled water, deionized water, pure water, and ultrapure water.

[0088] For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances. In order to solve the technical problem that a large amount of energy is consumed to grind the iron phosphate particles to nanoscale when preparing lithium iron phosphate in the prior art, and the energy consumption is large, the present application provides an iron phosphate material and a preparation method thereof, a positive electrode material, a positive electrode sheet, a secondary battery and an electrical device, wherein the iron phosphate material adopts a small-sized iron phosphate particle material with a ring structure and a D50 particle size of less than 1 μm, and is used as a precursor to prepare lithium iron phosphate, so that it is easier to obtain nano-scale iron phosphate materials, reduce the energy consumption required for nano-ization, and it is easier to obtain iron phosphate materials with smaller particle sizes, so that it is easier to improve the conductivity of the prepared lithium iron phosphate material, and then the energy consumption and cost in the preparation process of the positive electrode sheet, the secondary battery and the electrical device are also reduced, and the electrochemical performance is improved.

[0089] The electric device provided in the embodiment of the present application may be, but is not limited to, a mobile phone, a tablet, a laptop computer, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.

[0090] Please refer to Figure 1 and Figure 2In the first aspect, the embodiment of the present application provides an iron phosphate material, the iron phosphate material includes iron phosphate particles, the iron phosphate particles have a ring structure, and the D50 particle size of the iron phosphate particles is less than 1 μm. Among them, the D50 particle size of the iron phosphate particles can be 10nm, 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, of course, it can also be other values ​​within the above range, preferably 750nm to 860nm. The iron phosphate material uses the above-mentioned small-sized iron phosphate particle material with a ring structure and a D50 particle size of less than 1 μm as a precursor to prepare lithium iron phosphate, which is beneficial to reduce the energy consumption required for nano-sizing and make it easier to obtain iron phosphate materials with smaller particle sizes, thereby making it easier to improve the conductivity of the prepared lithium iron phosphate material.

[0091] Furthermore, in some embodiments, the aggregation index of the particle size of the iron phosphate particles satisfies: 0.5≤(D90-D10) / D50≤2, preferably 1.25≤(D90-D10) / D50≤1.81.

[0092] In the technical solution of the embodiment of the present application, the particle size distribution of the iron phosphate particles is more concentrated, which is conducive to improving the grinding efficiency and obtaining nano-scale iron phosphate particles with uniform size by sand grinding, so that in the subsequent lithium iron phosphate preparation process, lithium ions are evenly distributed in the iron phosphate particles, and lithium iron phosphate materials with high conductivity and excellent electrochemical properties are obtained.

[0093] Furthermore, in some embodiments, the ratio of the average inner diameter to the average outer diameter of the annular structure of the iron phosphate particles is (0.35-0.48):1, preferably (0.36-0.43):1.

[0094] In the technical solution of the embodiment of the present application, the ring diameter (the distance between the outer diameter and the inner diameter of the ring) affects the grinding efficiency and the morphology of the grinding particles. A ring diameter that is too large is not conducive to improving the grinding efficiency, and a ring diameter that is too small is prone to irregular fractures during the grinding process. Iron phosphate particles within the above-mentioned size range are conducive to improving the grinding efficiency and obtaining small nano-scale iron phosphate particles with regular morphology and uniform size, so that lithium ions are evenly distributed in the iron phosphate particles during the subsequent preparation of lithium iron phosphate.

[0095] It should be noted that in the technical solution of the embodiment of the present application, the inner diameter of the annular structure of the iron phosphate particle refers to the distance between the straight line passing through the center of the annular structure of the iron phosphate particle in the radial direction and the two points farthest from each other in the intersection of the iron phosphate particle, and the outer diameter of the annular structure of the iron phosphate particle refers to the distance between the straight line passing through the center of the annular structure of the iron phosphate particle in the radial direction and the two points closest to each other in the intersection of the iron phosphate particle.

[0096] Preferably, in some embodiments, the average inner diameter of the annular structure of the iron phosphate particles ranges from 178nm to 559nm, and the average outer diameter of the annular structure of the iron phosphate particles ranges from 474.60nm to 1188.90nm; preferably, the average inner diameter of the annular structure of the iron phosphate particles ranges from 240nm to 371nm, and the average outer diameter of the annular structure of the iron phosphate particles ranges from 614nm to 901nm.

[0097] In the technical solution of the embodiment of the present application, the iron phosphate particles within the above-mentioned size range are conducive to improving the grinding efficiency and obtaining nano-scale iron phosphate particles with regular morphology and uniform size.

[0098] Furthermore, in some embodiments, the specific surface area of ​​the iron phosphate particles is 13 m 2 / g~20m 2 / g, preferably 13m 2 / g~17m 2 / g.

[0099] In the technical solution of the embodiment of the present application, in the process of preparing lithium iron phosphate, the iron phosphate with a larger specific surface area of ​​the iron phosphate particles is conducive to the uniform mixing of the raw materials in the preparation process of lithium iron phosphate, and is conducive to the uniform distribution of lithium ions in the iron phosphate material, and is also conducive to improving the efficiency of lithium ion deintercalation, and improving the rate performance and specific capacity of lithium iron phosphate. The present application controls the specific surface area of ​​the iron phosphate material to be within the above range, which is conducive to grinding to obtain nano-scale iron phosphate particles with a high specific surface area, thereby preparing lithium iron phosphate materials with high rate performance and high specific capacity.

[0100] like Figure 3 As shown, in the second aspect, the embodiment of the present application provides a method for preparing an iron phosphate material, comprising the following steps:

[0101] preparing an iron-phosphorus solution comprising a ferrous ion source, a chloride ion source, and a phosphate ion source, wherein the pH value of the iron-phosphorus solution is not greater than 1.5;

[0102] The iron-phosphorus solution is heated to above 70° C., and then an oxidant is added to the iron-phosphorus solution to obtain an iron phosphate slurry;

[0103] The ferric phosphate slurry is heated to boiling, and after the ferric phosphate slurry changes color, the boiling state is maintained for 1.5 hours to 4 hours to obtain a first slurry;

[0104] Mixing the first slurry with low-temperature dilution water to obtain a second slurry;

[0105] The second slurry is subjected to solid-liquid separation to obtain an iron phosphate material.

[0106] Among them, in the technical scheme of the embodiment of the present application, the system for preparing the iron phosphate material adopts a chloride ion system, the pH value of the iron-phosphorus solution is controlled to inhibit the hydrolysis of ferrous ions and reduce the agglomeration of subsequently generated ferric phosphate ions, the temperature of the iron-phosphorus solution is controlled and the ferrous ions are oxidized to obtain an iron phosphate-containing slurry, and then the iron phosphate slurry is heated to boiling, and the volatility and complexing properties of hydrogen chloride are used to form an iron phosphate-hydrochloric acid complex with the iron phosphate particles in the iron phosphate slurry, and then low-temperature dilution water is added to the first slurry, and the iron phosphate particles with a D50 particle size of less than 1 μm and a ring structure are finally prepared through dilution-cold excitation decomposition complexation, so that it is easier to obtain nano-scale iron phosphate materials. When the iron phosphate material is used as a precursor to prepare lithium iron phosphate, it is beneficial to reduce the energy consumption required for nano-ization and it is easier to obtain iron phosphate materials with smaller particle sizes, thereby making it easier to improve the conductivity of the prepared lithium iron phosphate material. By forming a complex of ferric phosphate-hydrochloric acid under high temperature conditions, ferric phosphate is protected in the form of a complex to avoid particle agglomeration, and then a dilution-cold excitation decomplexation method is adopted, and the slurry containing ferric phosphate-hydrochloric acid is decomplexed under low temperature conditions, and the principle of cold quenching is used to further refine the ferric phosphate particles to generate small-sized ferric phosphate particles, and it is easier to obtain nano-scale ferric phosphate materials, reduce the energy consumption required for nano-ization, and it is easier to obtain ferric phosphate materials with smaller particle sizes, and improve the conductivity of lithium iron phosphate materials prepared by the ferric phosphate material. In addition, the method of high temperature boiling is adopted, which is conducive to the full complexation of ferric phosphate particles to form a complex of ferric phosphate-hydrochloric acid, and the free hydrochloric acid in the reaction system is evaporated to reduce the acidity, so as to facilitate the subsequent acquisition of small-sized and high-yield ferric phosphate, and realize the recovery of free hydrochloric acid. The preparation method in this application can be used to prepare the ferric phosphate material as described above, and the yield of preparing the ferric phosphate material is high, and the recovery of free hydrochloric acid can be realized.

[0107] Furthermore, in some embodiments, the molar ratio of iron, phosphorus and chlorine in the iron-phosphorus solution is (0.8-1.2):(0.8-2):(0.5-3).

[0108] In the technical solution of the embodiment of the present application, the iron element, phosphorus element and chlorine element in the reaction system affect the yield, size and morphology of the generated iron phosphate. For example, a higher iron-chlorine ratio and phosphorus-chlorine ratio are conducive to the precipitation of iron phosphate to obtain a higher iron phosphate yield. A smaller phosphorus-chlorine ratio is conducive to the formation of an iron phosphate-hydrochloric acid complex in the high-temperature boiling stage, reducing the agglomeration of iron phosphate to obtain an iron phosphate material with a smaller size and good dispersion. By controlling the iron element, phosphorus element and chlorine element to be within the above-mentioned proportion range, an iron phosphate material with a ring structure and a D50 particle size of less than 1 μm can be obtained with a higher yield.

[0109] In some embodiments, the molar ratio of the iron element, the phosphorus element, and the chlorine element in the iron-phosphorus solution is 1:(1-1.2):(2-3).

[0110] In the technical solution of the embodiment of the present application, controlling the iron, phosphorus and chlorine elements within the above range is conducive to sufficient precipitation of the iron element to form iron phosphate to obtain a higher yield, and the obtained iron phosphate material has a regular morphology and good particle dispersion.

[0111] In some embodiments, the oxidant is selected from an aqueous solution of hydrogen peroxide, the molar ratio of hydrogen peroxide in the aqueous solution of hydrogen peroxide to the iron element in the iron-phosphorus solution is (0.6-1):1, and the concentration of the iron element in the iron-phosphorus solution is 0.5 mol / L-2.0 mol / L.

[0112] In the technical solution of the embodiment of the present application, the ratio of hydrogen peroxide to the iron element in the iron-phosphorus solution and the concentration of the iron element affect the oxidation rate of ferrous ions, thereby affecting the nucleation rate of iron phosphate and the growth rate of crystals. Under the above conditions, it is beneficial to obtain an iron phosphate slurry with smaller iron phosphate particles, to generate more iron phosphate-hydrochloric acid complexes in the subsequent high-temperature boiling stage, and to stably and evenly disperse the iron phosphate-hydrochloric acid complexes in the first slurry, thereby reducing the agglomeration of iron phosphate particles, thereby generating small-sized iron phosphate materials with good particle dispersion in the subsequent dilution-cold excitation decomposition complexation stage.

[0113] In some embodiments, the aqueous solution of hydrogen peroxide is added to the iron-phosphorus solution by dropwise addition, and the dropwise addition time is 5 min to 15 min. After the dropwise addition is completed, the solution is stirred for 5 min to 15 min to obtain an iron phosphate slurry.

[0114] In the technical solution of the embodiment of the present application, the hydrogen peroxide dripping acceleration and stirring time affect the formation of iron phosphate crystal nuclei and the growth of crystals. Under the above conditions, it is beneficial to quickly generate iron phosphate crystal nuclei and inhibit crystal growth, thereby generating an iron phosphate slurry with smaller iron phosphate particles, so that more iron phosphate-hydrochloric acid complexes can be generated in the subsequent high-temperature boiling stage, and it is beneficial for the iron phosphate-hydrochloric acid complexes to be stably and evenly dispersed in the first slurry, reducing the agglomeration of iron phosphate particles, thereby generating small-sized iron phosphate materials with good particle dispersion in the subsequent dilution-cold excitation decomposition complexation stage.

[0115] In some embodiments, the iron-phosphorus solution is heated to 70° C. to 80° C., and then an aqueous solution of hydrogen peroxide is added to the iron-phosphorus solution.

[0116] In the technical solution of the embodiment of the present application, an aqueous solution of hydrogen peroxide is used and the temperature of the iron-phosphorus solution is controlled at 70°C to 80°C, which is conducive to the full reaction of hydrogen peroxide with the iron-phosphorus solution, improves the oxidation efficiency of ferrous ions, and facilitates the rapid generation of a large number of small-sized iron phosphate particles at this stage, which is conducive to the subsequent high-temperature boiling stage. More iron phosphate-hydrochloric acid complexes are generated, and the iron phosphate-hydrochloric acid complexes are stably and evenly dispersed in the first slurry, thereby preparing a small-sized iron phosphate material with good particle dispersibility.

[0117] In some embodiments, the mass fraction of hydrogen peroxide in the aqueous solution of hydrogen peroxide is 20% to 30%.

[0118] In the technical solution of the embodiment of the present application, the hydrogen peroxide is within the above content range, which is convenient for quickly generating iron phosphate particles and can effectively reduce the decomposition loss of hydrogen peroxide itself during the oxidation process of ferrous ions.

[0119] In some embodiments, the ferrous ion source is selected from one or more of ferrous nitrate and ferrous chloride.

[0120] In the technical scheme of the embodiment of the present application, the above-mentioned ferrous ion sources can provide the necessary ferrous ions for the iron-phosphorus solution reaction system. Taking ferrous nitrate as the ferrous salt, the free nitrate ions in the system can form nitric acid and volatilize and remove in the subsequent boiling process. Taking ferrous chloride as the ferrous salt, the free chloride ions in the system can be volatilized and removed in the form of hydrochloric acid in the subsequent boiling process, so as to reduce the acidity of the system and reduce impurities, and is conducive to the subsequent acquisition of small-sized and high-yield iron phosphate.

[0121] In some embodiments, the source of ferrous ions is selected from ferrous chloride.

[0122] In the technical solution of the embodiment of the present application, ferrous chloride introduces chloride ions while providing ferrous ions, so that they can subsequently complex with iron phosphate particles to form an iron phosphate-hydrochloric acid complex, thereby reducing the agglomeration of iron phosphate and avoiding the introduction of impurities such as nitrogen and oxygen.

[0123] In some embodiments, the chloride ion source is selected from at least one of hydrochloric acid and ferrous chloride.

[0124] In the technical solution of the embodiment of the present application, hydrochloric acid and ferrous chloride can both provide the chloride ions required for the reaction and reduce the introduction of other impurity cations.

[0125] In some embodiments, the phosphate ion source is selected from H 3 PO 4 NH 4 )H 2 PO 4 NH 4 ) 2HPO 4 At least one of .

[0126] In the technical solution of the embodiment of the present application, H 3 PO 4 NH 4 )H 2 PO 4 NH 4 ) 2 HPO 4 It can provide the necessary phosphate ions for the reaction.

[0127] In some embodiments, the steps for preparing the iron-phosphorus solution are as follows:

[0128] A ferrous ion source, a chloride ion source, a phosphate ion source and water are mixed and the pH value of the mixed system is controlled to be no greater than 1.5 to obtain an iron-phosphorus solution.

[0129] In this embodiment, the desired iron-phosphorus solution can be obtained by directly mixing the ferrous ion source, the chloride ion source, the phosphate ion source and water, and the process is simple.

[0130] In some embodiments, the ferrous ion source is ferrous chloride, the chloride ion source is selected from ferrous chloride and hydrochloric acid, and the phosphate ion source is phosphoric acid.

[0131] In the technical solution of the embodiment of the present application, ferrous chloride is used as both a ferrous ion source and a chloride ion source, hydrochloric acid is used as a chloride ion source and provides acidity conditions for the reaction, and phosphate is used as a phosphorus source and can provide acidity conditions for the reaction. The pH value of the system and the ratio of ferrous ions, phosphate ions, and chloride ions can be controlled by the ratio of the above raw materials. No additional acid or alkali (such as sulfuric acid, nitric acid, sodium hydroxide, ammonia water, etc.) is required. While preparing an iron phosphate material with a ring structure and a smaller size, the impurity ions (such as sulfate, nitrate, sodium, NH4+) can be minimized. 4 The introduction of high-purity iron phosphate materials can improve the cycle life and capacity retention rate of lithium iron phosphate prepared with the iron phosphate materials as raw materials in batteries.

[0132] In some embodiments, the steps for preparing the iron-phosphorus solution are as follows:

[0133] Heat the dilute hydrochloric acid aqueous solution to 50°C to 70°C, then add the elemental iron material to react to obtain a ferrous chloride solution, wherein the concentration of the dilute hydrochloric acid aqueous solution is 1.0 mol / L to 4.0 mol / L;

[0134] Phosphoric acid and water are added to the ferrous chloride solution, mixed and the pH value is controlled to be no greater than 1.5 to obtain an iron-phosphorus solution.

[0135] In the technical scheme of the embodiment of the present application, an iron-phosphorus solution is prepared by using an elemental iron material, an aqueous hydrochloric acid solution and phosphoric acid as raw materials, which can minimize the introduction of impurity ions and prepare a high-purity iron phosphate material. Specifically, phosphoric acid and water can be added to a ferrous chloride solution in the form of an aqueous phosphoric acid solution, or they can be added to a ferrous chloride solution separately. Specifically, in some embodiments, the elemental iron material is selected from one or more of iron sheet, iron powder and iron block.

[0136] Furthermore, in some embodiments, the pH value of the iron-phosphorus solution is 0.2-1.5.

[0137] In the technical solution of the embodiment of the present application, the pH value of the iron-phosphorus solution affects the generation rate and yield of iron phosphate. A higher pH value easily causes a large number of iron phosphate particles to agglomerate during the oxidation stage, while a lower pH value is not conducive to the precipitation of the target product, iron phosphate. Within the above-mentioned pH value range, it is more conducive to obtaining high-yield and smaller-sized iron phosphate materials.

[0138] In some embodiments, the temperature difference between the second slurry and the first slurry is no less than 60°C.

[0139] In the technical solution of the embodiment of the present application, the higher temperature difference is more conducive to the iron phosphate-hydrochloric acid decomplexation and cold quenching and refinement, thereby generating a smaller size of iron phosphate material.

[0140] In some embodiments, the temperature difference between the second slurry and the first slurry is 70°C to 90°C.

[0141] In the technical solution of the embodiment of the present application, the temperature difference between the second slurry and the first slurry is controlled within the temperature range, which is more conducive to obtaining smaller-sized iron phosphate materials and obtaining a higher yield.

[0142] In some embodiments, the mass ratio of the first slurry to the low-temperature dilution water is 1:(10-20).

[0143] In the technical solution of the embodiment of the present application, low-temperature dilution water is used to quickly cool down and dilute the system, which is beneficial to the decomplexation of the iron phosphate-hydrochloric acid complex to generate iron phosphate material. The mass ratio of the first slurry to the low-temperature dilution water is within the above-mentioned range, which is beneficial to the rapid and sufficient decomplexation of the iron phosphate-hydrochloric acid complex, thereby obtaining a small-sized iron phosphate material with higher purity and higher yield.

[0144] In some embodiments, the first slurry is mixed with low-temperature dilution water and stirred until it changes color to obtain a second slurry.

[0145] In the technical solution of the embodiment of the present application, during the high-temperature boiling treatment, an iron phosphate-hydrochloric acid complex is generated. After adding low-temperature dilution water and mixing, the iron phosphate is precipitated after decomplexation, and the color of the slurry changes. Specifically, the color of the iron phosphate is off-white or light red powder, and the iron phosphate slurry containing iron phosphate particles obtained by oxidation with an oxidant is brownish yellow. The brownish yellow iron phosphate slurry is treated with high-temperature boiling (acid removal) and no obvious iron phosphate precipitation is precipitated, and the slurry color is bright yellow, indicating that during the high-temperature boiling treatment, an iron phosphate-hydrochloric acid complex (e.g., [FeCl 4 ]-complex), after adding low-temperature dilution water and mixing, the iron phosphate is decomplexed and precipitated, and the slurry color changes from bright yellow to light white.

[0146] In some embodiments, the second slurry is subjected to solid-liquid separation, and the obtained solid is washed and then dried at 90° C. to 120° C. to obtain the iron phosphate material.

[0147] In the technical solution of the embodiment of the present application, water can be quickly removed under the above conditions to obtain the iron phosphate material.

[0148] In a third aspect, an embodiment of the present application provides a positive electrode material, including at least one of a lithium iron phosphate material and a lithium iron manganese phosphate material. The lithium iron phosphate material is prepared from the above iron phosphate material or from an iron phosphate material prepared by the above method for preparing the iron phosphate material. The lithium iron manganese phosphate material is prepared from the above iron phosphate material or from an iron phosphate material prepared by the above method for preparing the iron phosphate material.

[0149] In a fourth aspect, an embodiment of the present application provides a positive electrode sheet, which includes the positive electrode material mentioned above. The positive electrode sheet includes the positive electrode material mentioned above, thereby having the advantages of reducing the energy consumption and cost of preparing the positive electrode sheet.

[0150] In a fifth aspect, the present application provides a secondary battery, wherein the positive electrode is the positive electrode. The secondary battery includes the positive electrode, thereby reducing the energy consumption and cost of the secondary battery and improving the electrochemical performance of the secondary battery.

[0151] In a sixth aspect, the present application provides an electric device, such as a vehicle, comprising a battery as described in the above embodiment. The electric device includes the above secondary battery, thereby having the advantages of reducing the energy consumption and cost of the electric device and improving the electrochemical performance of the electric device.

[0152] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0153] 1. Preparation method

[0154] Example 1

[0155] Step 1, preparation of ferrous chloride: take concentrated hydrochloric acid, add pure water to prepare a hydrochloric acid solution with a chloride ion concentration of 4.0 mol / L for later use, heat the dilute hydrochloric acid solution to 60°C, add iron powder to the dilute hydrochloric acid solution after reaching the temperature (wherein the iron powder is added according to the molar ratio of Fe element to Cl element of 1:2), react until no bubbles are generated, filter, and obtain ferrous chloride solution.

[0156] Step 2, preparation of iron-phosphorus solution: take the prepared ferrous chloride solution, add phosphoric acid and pure water to mix, prepare an iron-phosphorus solution with a ferrous ion concentration of 1.5 mol / L (wherein phosphoric acid is added according to the molar ratio of Fe element to P element of 1:1), stir evenly to obtain an iron-phosphorus solution, and the pH value of the iron-phosphorus solution is 0.80.

[0157] Step 3, preparation of iron phosphate slurry: take the iron-phosphorus solution prepared in step 2 as the base liquid, heat the base liquid to 80°C, and add hydrogen peroxide (the mass fraction of hydrogen peroxide in hydrogen peroxide is 28%) to the base liquid after reaching the temperature. 2 O 2 The molar ratio of the molar mass of the Fe element to the molar mass of the Fe element is 1.5:2.0), the dropping time is controlled to be 10 min, and the stirring is continued for 10 min after the dropping is completed to obtain the iron phosphate slurry.

[0158] Step 4: Heat the ferric phosphate slurry prepared in step 3 to boiling, and after the color of the ferric phosphate slurry changes from brown-yellow to bright yellow, continue to maintain the boiling state for 2 hours to obtain the first slurry.

[0159] Step 5, adding the first slurry prepared in step 4 into low-temperature dilution water, stirring until the color of the slurry changes from bright yellow to light white, to obtain a second slurry (wherein the temperature of the second slurry is 20°C, and the mass ratio of the first slurry to the low-temperature dilution water is 1:12).

[0160] Step six, filtering the second slurry prepared in step five, washing the solids obtained by filtration in countercurrent until the conductivity of the washing water after washing is less than 500 us / cm to obtain an iron phosphate filter cake, and drying the filter cake at 98° C. to obtain iron phosphate.

[0161] The SEM results of the iron phosphate material prepared in Example 1 are as follows: Figure 1 and Figure 2 As shown in Figure 1, the microstructure of the iron phosphate material is ring-shaped and the particle dispersion is good. The XRD results of the iron phosphate material are shown in Figure 1. Figure 4 As shown, the prepared small-sized iron phosphate material with a ring structure is a single iron phosphate phase. According to the particle size detection data, the D50 particle size of the iron phosphate material is 0.82 μm, and the D100 particle size is only 3.846 μm. The embodiment of the present application prepared a small-sized iron phosphate material with a D50 particle size of less than 1 μm and a ring structure.

[0162] Example 2

[0163] Step 1, preparation of ferrous chloride: take concentrated hydrochloric acid, add pure water to prepare a hydrochloric acid solution with a chloride ion concentration of 4.0 mol / L for later use, heat the dilute hydrochloric acid solution to 50°C, add iron powder to the dilute hydrochloric acid solution after reaching the temperature (wherein the iron powder is added according to the molar ratio of Fe element to Cl element of 1:2), react until no bubbles are generated, filter, and obtain ferrous chloride solution.

[0164] Step 2, preparation of iron-phosphorus solution: take the prepared ferrous chloride solution, add phosphoric acid and pure water to mix, prepare an iron-phosphorus solution with a ferrous ion concentration of 0.5 mol / L (wherein phosphoric acid is added according to the molar ratio of Fe element to P element of 1.0:1), stir evenly to obtain an iron-phosphorus solution, and the pH value of the iron-phosphorus solution is 1.2.

[0165] Step 3, preparation of iron phosphate slurry: take the iron-phosphorus solution prepared in step 2 as the base liquid, heat the base liquid to 70°C, and add hydrogen peroxide (the mass fraction of hydrogen peroxide in hydrogen peroxide is 20%, and the hydrogen peroxide is adjusted according to H 2 O 2 The molar ratio of the molar amount of the Fe element to the molar amount of the Fe element is 0.6:1), the dropping time is controlled to be 5 min, and the stirring is continued for 5 min after the dropping is completed to obtain the iron phosphate slurry.

[0166] Step 4: Heat the ferric phosphate slurry prepared in step 3 to boiling, and after the color of the ferric phosphate slurry changes from brown-yellow to bright yellow, continue to maintain the boiling state for 1.5 hours to obtain the first slurry.

[0167] Step 5, adding the first slurry prepared in step 4 into low-temperature dilution water, stirring until the color of the slurry changes from bright yellow to light white, to obtain a second slurry (wherein the temperature of the second slurry is 10° C., and the mass ratio of the first slurry to the low-temperature dilution water is 1:30).

[0168] Step six, filtering the second slurry prepared in step five, washing the solids obtained by filtration in countercurrent until the conductivity of the washing water after washing is less than 500 us / cm to obtain an iron phosphate filter cake, and drying the filter cake at 90° C. to obtain iron phosphate.

[0169] Example 3

[0170] Step 1, preparation of ferrous chloride: take concentrated hydrochloric acid, add pure water to prepare a hydrochloric acid solution with a chloride ion concentration of 4.0 mol / L for standby use, heat the dilute hydrochloric acid solution to 70°C, add iron powder to the dilute hydrochloric acid solution after reaching the temperature (wherein the iron powder is added according to the molar ratio of Fe element to Cl element of 1:2), react until no bubbles are generated, filter, and obtain ferrous chloride solution.

[0171] Step 2, preparation of iron-phosphorus solution: take the prepared ferrous chloride solution, add phosphoric acid and pure water to mix, prepare an iron-phosphorus solution with a ferrous ion concentration of 2 mol / L (wherein phosphoric acid is added according to the molar ratio of Fe element to P element of 1:1), stir evenly to obtain an iron-phosphorus solution, and the pH value of the iron-phosphorus solution is 0.6.

[0172] Step 3, preparation of iron phosphate slurry: take the iron-phosphorus solution prepared in step 2 as the base liquid, heat the base liquid to 80°C, and add hydrogen peroxide (the mass fraction of hydrogen peroxide in hydrogen peroxide is 28%) to the base liquid after reaching the temperature. 2 O 2 The molar ratio of the molar mass of the Fe element to the molar mass of the Fe element is 1:1), the dropping time is controlled to be 15 min, and the stirring is continued for 15 min after the dropping is completed to obtain iron phosphate slurry.

[0173] Step 4: Heat the ferric phosphate slurry prepared in step 3 to boiling, and after the color of the ferric phosphate slurry changes from brown-yellow to bright yellow, continue to maintain the boiling state for 4 hours to obtain the first slurry.

[0174] Step 5, adding the first slurry prepared in step 4 into low-temperature dilution water, stirring until the color of the slurry changes from bright yellow to light white, to obtain a second slurry (wherein the temperature of the second slurry is 30° C., and the mass ratio of the first slurry to the low-temperature dilution water is 1:10).

[0175] Step six, filtering the second slurry prepared in step five, washing the solids obtained by filtration in countercurrent until the conductivity of the washing water after washing is less than 500 us / cm to obtain an iron phosphate filter cake, and drying the filter cake at 120° C. to obtain iron phosphate.

[0176] Example 4

[0177] Step 1: Preparation of iron-phosphorus solution: Mix ferrous chloride, hydrochloric acid and H 3 PO 4and pure water to obtain an iron-phosphorus solution with a ferrous ion concentration of 1.5 mol / L (wherein ferrous chloride, H 3 PO 4 and hydrochloric acid according to the molar ratio of Fe element, P element and Cl element of 1:1:3, and after stirring evenly, an iron-phosphorus solution is obtained, and the pH value of the iron-phosphorus solution is 0.3.

[0178] Step 2, preparation of iron phosphate slurry: take the iron-phosphorus solution prepared in step 1 as the base liquid, heat the base liquid to 80°C, and add hydrogen peroxide (the mass fraction of hydrogen peroxide in hydrogen peroxide is 28%) to the base liquid after reaching the temperature. 2 O 2 The molar ratio of the molar mass of the Fe element to the molar mass of the Fe element is 1.5:2.0), the dropping time is controlled to be 10 min, and the stirring is continued for 10 min after the dropping is completed to obtain the iron phosphate slurry.

[0179] Step three, heating the iron phosphate slurry prepared in step two to boiling, and after the color of the iron phosphate slurry gradually changes from brown-yellow to bright yellow, continue to maintain the boiling state for 2 hours to obtain the first slurry.

[0180] Step 4: Add the first slurry prepared in step 3 into low-temperature dilution water and stir until the color of the slurry changes from bright yellow to light white to obtain a second slurry (wherein the temperature of the second slurry is 20° C., and the mass ratio of the first slurry to the low-temperature dilution water is 1:12).

[0181] Step 5: Filter the second slurry prepared in step 4, and wash the solids obtained by filtration in countercurrent until the conductivity of the washing water after washing is less than 500 us / cm to obtain an iron phosphate filter cake, and dry the filter cake at 98° C. to obtain iron phosphate.

[0182] Example 5

[0183] Step 1: Preparation of iron-phosphorus solution: Mix ferrous nitrate, hydrochloric acid and (NH 4 )H 2 PO 4 and pure water to obtain an iron-phosphorus solution with a ferrous ion concentration of 1.5 mol / L (wherein ferrous nitrate, hydrochloric acid and (NH 4 )H 2 PO 4 The Fe element, the P element and the Cl element are added in a substance ratio of 1:1:3, and after being stirred evenly, an iron-phosphorus solution is obtained, and the pH value of the iron-phosphorus solution is 0.2.

[0184] Step 2, preparation of iron phosphate slurry: take the iron-phosphorus solution prepared in step 1 as the base liquid, heat the base liquid to 70°C, and add hydrogen peroxide (the mass fraction of hydrogen peroxide in hydrogen peroxide is 20%, and the hydrogen peroxide is adjusted according to H2 O 2 The molar ratio of the molar amount of the Fe element to the molar amount of the Fe element is 0.6:1), the dropping time is controlled to be 5 min, and the stirring is continued for 5 min after the dropping is completed to obtain the iron phosphate slurry.

[0185] Step three, heating the ferric phosphate slurry prepared in step two to boiling, and after the color of the ferric phosphate slurry gradually changes from brown-yellow to bright yellow, continue to maintain the boiling state for 1.5 hours to obtain the first slurry.

[0186] Step 4: Add the first slurry prepared in step 3 into low-temperature dilution water and stir until the color of the slurry changes from bright yellow to light white to obtain a second slurry (wherein the temperature of the second slurry is 10° C., and the mass ratio of the first slurry to the low-temperature dilution water is 1:30).

[0187] Step 5: Filter the second slurry prepared in step 4, and wash the solids obtained by filtration in countercurrent until the conductivity of the washing water is less than 500 us / cm to obtain an iron phosphate filter cake, and dry the filter cake at 90° C. to obtain iron phosphate.

[0188] Example 6

[0189] Step 1: Preparation of iron-phosphorus solution: Mix ferrous nitrate, hydrochloric acid and (NH 4 ) 2 HPO 4 and pure water to obtain an iron-phosphorus solution with a ferrous ion concentration of 2 mol / L (wherein ferrous nitrate, hydrochloric acid and (NH 4 ) 2 HPO 4 The Fe element, the P element and the Cl element are added in a substance ratio of 1.0:1.2:3, and after being stirred evenly, an iron-phosphorus solution is obtained, and the pH value of the iron-phosphorus solution is 0.4.

[0190] Step 2, preparation of iron phosphate slurry: take the iron-phosphorus solution prepared in step 1 as the base liquid, heat the base liquid to 80°C, and add hydrogen peroxide (the mass fraction of hydrogen peroxide in hydrogen peroxide is 28%) to the base liquid after reaching the temperature. 2 O 2 The molar ratio of the molar mass of the Fe element to the molar mass of the Fe element is 1:1), the dropping time is controlled to be 15 min, and the stirring is continued for 15 min after the dropping is completed to obtain iron phosphate slurry.

[0191] Step three, heating the iron phosphate slurry prepared in step two to boiling, and after the color of the iron phosphate slurry gradually changes from brown-yellow to bright yellow, continue to maintain the boiling state for 4 hours to obtain the first slurry.

[0192] Step 4: Add the first slurry prepared in step 3 into low-temperature dilution water and stir until the color of the slurry changes from bright yellow to light white to obtain a second slurry (wherein the temperature of the second slurry is 30° C., and the mass ratio of the first slurry to the low-temperature dilution water is 1:10).

[0193] Step 5: Filter the second slurry prepared in step 4, and wash the solids obtained by filtration in countercurrent until the conductivity of the washing water after washing is less than 500 us / cm to obtain an iron phosphate filter cake, and dry the filter cake at 120° C. to obtain iron phosphate.

[0194] Example 7

[0195] The only difference between it and Example 4 is that in step 1, ferrous chloride is replaced by ferrous nitrate.

[0196] Example 8

[0197] The only difference between it and Example 4 is that in step 1, ferrous chloride is replaced by ferrous nitrate and ferrous nitrate, H 3 PO 4 And hydrochloric acid is added according to the molar ratio of Fe element, P element and Cl element of 1:1:2. Step 1 is as follows:

[0198] Step 1: Preparation of iron-phosphorus solution: Mix ferrous nitrate, hydrochloric acid and H 3 PO 4 and pure water to obtain an iron-phosphorus solution with a ferrous ion concentration of 1.5 mol / L (wherein ferrous nitrate, H 3 PO 4 and hydrochloric acid according to the molar ratio of Fe element, P element and Cl element of 1:1:2, and after stirring evenly, an iron-phosphorus solution is obtained, and the pH value of the iron-phosphorus solution is 0.45.

[0199] Example 9

[0200] The only difference between it and Example 4 is that in step 1, ferrous chloride is replaced by ferrous nitrate and ferrous nitrate, H 3 PO 4 And hydrochloric acid is added according to the molar ratio of Fe element, P element and Cl element of 1:1:0.5. Step 1 is as follows:

[0201] Step 1: Preparation of iron-phosphorus solution: Mix ferrous nitrate, hydrochloric acid and H 3 PO 4 and pure water to obtain an iron-phosphorus solution with a ferrous ion concentration of 1.5 mol / L (wherein ferrous nitrate, H 3 PO 4and hydrochloric acid according to the molar ratio of Fe element, P element and Cl element of 1:1:0.5, and after stirring evenly, an iron-phosphorus solution is obtained, and the pH value of the iron-phosphorus solution is 0.55.

[0202] Example 10

[0203] The only difference between it and Example 4 is that in step 1, ferrous chloride is replaced by ferrous nitrate and ferrous nitrate, H 3 PO 4 And hydrochloric acid is added according to the molar ratio of Fe element, P element and Cl element of 1:1:4. Step 1 is as follows:

[0204] Step 1: Preparation of iron-phosphorus solution: Mix ferrous nitrate, hydrochloric acid and H 3 PO 4 and pure water to obtain an iron-phosphorus solution with a ferrous ion concentration of 1.5 mol / L (wherein ferrous nitrate, H 3 PO 4 and hydrochloric acid according to the molar ratio of Fe element, P element and Cl element of 1:1:4, and after stirring evenly, an iron-phosphorus solution is obtained, and the pH value of the iron-phosphorus solution is 0.25.

[0205] Embodiment 11

[0206] The only difference between it and Example 4 is that the dropping time in step 2 is controlled to 25 min, and stirring is continued for 25 min after the dropping is completed.

[0207] Example 12

[0208] The only difference between it and Example 4 is that in step 3, the temperature of the second slurry is controlled to be 50°C.

[0209] Comparative Example 1

[0210] The only difference between it and Example 4 is that in step one, ferrous chloride is replaced by ferrous nitrate, and hydrochloric acid is replaced by nitric acid; in step three, the ferric phosphate slurry prepared in step two is heated to boiling and maintained at a boiling state for 2 hours to obtain a first slurry.

[0211] Comparative Example 2

[0212] The only difference between the embodiment 4 and the embodiment 4 is that the step 1 also includes adjusting the pH value of the iron-phosphorus solution to 2 with an alkali solution, and the specific steps of the step 1 are as follows:

[0213] Ferrous chloride, hydrochloric acid and H 3 PO 4 and pure water to obtain an iron-phosphorus solution with a ferrous ion concentration of 1.5 mol / L (wherein ferrous chloride, H 3 PO4 and hydrochloric acid according to the molar ratio of Fe element, P element and Cl element of 1:1:3), stirring evenly to obtain an iron-phosphorus solution, to which 1 mol / L sodium hydroxide aqueous solution is added dropwise to adjust the pH of the iron-phosphorus solution to 2.

[0214] Comparative Example 3

[0215] The only difference between this embodiment and embodiment 4 is that in step 2, the base liquid is heated to a temperature of 65°C.

[0216] Comparative Example 4

[0217] The only difference between it and Example 4 is that in step 3, the boiling state is maintained for 30 minutes.

[0218] Comparative Example 5

[0219] The only difference between it and Example 4 is that in step 4, low-temperature dilution water is not used, but the mixture is naturally cooled to room temperature to obtain the second slurry.

[0220] Comparative Example 6

[0221] The traditional iron method is used to prepare iron phosphate. The specific steps are as follows:

[0222] Step 1, preparation of ferrous dihydrogen phosphate: take phosphoric acid, add pure water to prepare a dilute phosphoric acid solution with a mass fraction of 30% for standby use, heat the dilute phosphoric acid solution to 50°C, add an appropriate amount of iron powder to the dilute phosphoric acid solution after reaching the temperature (wherein the iron powder is added according to the molar ratio of Fe element to phosphorus element of 1:2), filter the slurry after the reaction is completed, and obtain the ferrous dihydrogen phosphate solution.

[0223] Step 2, preparation of ferric phosphate: take the ferrous dihydrogen phosphate solution prepared in step 1, add pure water to prepare a ferrous dihydrogen phosphate solution with a molar concentration of 1 mol / L, heat the prepared ferrous dihydrogen phosphate solution to 80° C., and after heating, evenly add hydrogen peroxide (the mass fraction of hydrogen peroxide in hydrogen peroxide is 28%, and the hydrogen peroxide is adjusted according to H 2 O 2 The molar ratio of the molar amount of the Fe element to the molar amount of the Fe element is 1.5:2.0), the dropping time is controlled to be 105 min, and after the dropping is completed, the temperature is kept for 60 min to obtain iron phosphate slurry.

[0224] Step three, filtering the iron phosphate slurry prepared in step two, and washing the filtrate by countercurrent until the conductivity of the washing water is less than 500 us / cm to obtain an iron phosphate filter cake, and drying the filter cake at 98° C. to obtain iron phosphate.

[0225] The SEM image of the iron phosphate material prepared in Comparative Example 6 is as follows: Figure 5 and Figure 6As shown, the microstructure is flaky, and the XRD pattern of iron phosphate material is as follows Figure 7 As shown, the prepared iron phosphate material is a single iron phosphate phase. According to the particle size detection data, the D50 particle size of the iron phosphate material prepared in Comparative Example 6 is 4.833 μm, and the D100 particle size is 15.721 μm, which is significantly higher than that of the iron phosphate material prepared in Example 1.

[0226] 2. Test Method

[0227] 1. Property test of iron phosphate materials

[0228] 1) The inner diameter and outer diameter of the material were characterized by a scanning electron microscope (SEM); wherein, the inner diameter of the iron phosphate material was counted and averaged to obtain the average inner diameter, and the outer diameter of the material was counted and averaged to obtain the average outer diameter. The average inner diameter, average outer diameter, and the ratio of the average inner diameter to the average outer diameter of the material are shown in Table 1.

[0229] 2) The materials were characterized by X-ray diffractometer.

[0230] 3) The specific surface area of ​​the material was tested by the nitrogen adsorption BET test method, with reference to the standard GB / T9587-2017. The test results of the specific surface area of ​​the iron phosphate materials prepared in the embodiment and the comparative example are shown in Table 1.

[0231] 4) The D0 particle size (μm), D10 particle size (μm), D50 particle size (μm), D90 particle size (μm), D99 particle size (μm), and D100 particle size (μm) of the material were measured by a laser particle size analyzer. The particle size distribution (D90-D10) / D50 and particle size test results are shown in Table 1.

[0232] 5) Sanding time test

[0233] The iron phosphate material was sand-milled until the D50 particle size of the material was 350 nm, and then the sand-milling was stopped and the sand-milling time was recorded.

[0234] 6) The elemental composition of the material was analyzed using an inductively coupled plasma spectrometer. The results are shown in Table 2.

[0235] III. Analysis of test results of various embodiments and comparative examples

[0236] Table 1

[0237]

[0238] Note: “ / ” in Table 1 indicates that the prepared iron phosphate material has a flaky structure and has no inner and outer diameter data.

[0239] Table 2

[0240]

[0241]

[0242] It can be seen from the data in Table 1 that the size of the iron phosphate materials prepared in Examples 1-12 of the present application is significantly smaller than the size of the iron phosphate materials prepared in Comparative Examples 1-6. Under the same conditions, the time required for sand milling to a D50 particle size of 350 nm for the iron phosphate materials prepared in Examples 1-12 of the present application is less than 100 min, which effectively reduces the energy consumption of the sand milling process and improves the process efficiency.

[0243] From the comparison between Example 4 and Comparative Example 1, it can be seen that compared with the case in which ferrous chloride and hydrochloric acid are replaced by ferrous nitrate and nitric acid respectively in Comparative Example 1, the size of the iron phosphate material obtained in Example 4 is significantly reduced, indicating that the full chloride ion system using ferrous chloride and hydrochloric acid as the ferrous ion source and the chloride ion source can make full use of the volatility and complexing property of hydrogen chloride to form an iron phosphate-hydrochloric acid complex with the iron phosphate particles in the iron phosphate slurry, and the iron phosphate is protected in the form of a complex to avoid agglomeration of the iron phosphate particles, and then the dilution-cold excitation decomplexation method is adopted to decomplex the slurry containing iron phosphate-hydrochloric acid under low temperature conditions, thereby facilitating the generation of small-sized iron phosphate particles.

[0244] From the comparison between Example 4 and Comparative Example 2, it can be seen that compared with Comparative Example 2 in which the pH value of the iron-phosphorus solution is 2 controlled by sodium hydroxide aqueous solution, the pH value of the iron-phosphorus solution is controlled to 0.3 in Example 4, and the size of the obtained iron phosphate material is significantly reduced, indicating that controlling the pH value of the iron-phosphorus solution to no more than 1.5 is conducive to obtaining smaller-sized iron phosphate materials.

[0245] It can be seen from Example 4 and Comparative Example 3 that, compared with Comparative Example 3, in Example 4, the iron-phosphorus solution is heated to above 70°C to prepare iron phosphate slurry, which improves the ferrous oxidation efficiency, facilitates the rapid generation of a large number of small-sized iron phosphate particles, is beneficial to the subsequent high-temperature boiling stage to generate more iron phosphate-hydrochloric acid complexes, and the iron phosphate-hydrochloric acid complexes are stably and evenly dispersed in the slurry, and the size of the obtained iron phosphate material is significantly reduced.

[0246] It can be seen from Example 4 and Comparative Example 4 that, compared with Comparative Example 4, maintaining a longer boiling state in Example 4 is beneficial to the full complexation of the iron phosphate particles in the system to form an iron phosphate-hydrochloric acid complex, and protecting the iron phosphate in the form of a complex to avoid agglomeration of the iron phosphate particles, thereby obtaining a smaller-sized iron phosphate material.

[0247] From Example 4 and Comparative Example 5, it can be seen that in Comparative Example 5, low-temperature dilution water is not added, the cold extraction effect is reduced, the overall size of the iron phosphate particles and the D50 particle size are significantly higher, and it takes a long time to sand grind to a D50 particle size of 350 nm.

[0248] It can be seen from Example 4 and Comparative Example 6 that the D50 particle size of the iron phosphate particles prepared by the traditional iron process route of Comparative Example 6 is larger and significantly higher than that of the iron phosphate material in Example 4.

[0249] From the comparison between Example 4 and Example 7, it can be seen that compared with Example 7 in which ferrous nitrate is used as the ferrous source, that is, nitrate anions and chloride anions are introduced simultaneously, the full chloride anion system adopted in Example 4 makes it easier to obtain smaller-sized iron phosphate materials.

[0250] Compared with Example 10, the D50 particle size, average inner diameter and average outer diameter of Examples 8 and 9, in which the molar ratio of iron, phosphorus and chlorine is within the range of (0.8-1.2):(0.8-2):(0.5-3), are significantly smaller than those of Example 10, which is more conducive to obtaining iron phosphate materials with a smaller overall size.

[0251] From the comparison between Example 4 and Example 11, it can be seen that the dripping time of hydrogen peroxide is controlled to be 5min to 15min and the stirring time is 5min to 15min, and a smaller size of iron phosphate material can be obtained. Compared with Example 11, Example 4 adopts the above-mentioned faster dripping speed and shorter stirring time, which is conducive to the rapid generation of iron phosphate crystal nuclei and the inhibition of crystal growth, thereby facilitating the generation of more iron phosphate-hydrochloric acid complexes in the subsequent high-temperature boiling stage, and maintaining the iron phosphate-hydrochloric acid complexes stably and evenly dispersed in the iron phosphate slurry, reducing the agglomeration of iron phosphate particles, thereby obtaining a smaller size of iron phosphate material.

[0252] From the comparison between Example 4 and Example 12, it can be seen that by controlling the temperature difference between the second slurry and the first slurry to be not less than 60° C., a smaller-sized iron phosphate material can be obtained. Compared with Example 12, Example 4 adopts a higher temperature difference, which is more conducive to iron phosphate-hydrochloric acid decomplexation and cold quenching refinement, thereby facilitating the generation of a smaller-sized iron phosphate material.

[0253] It can be seen from Table 2 that compared with Comparative Example 6, the metal impurity content of the iron phosphate materials prepared in Examples 1-12 of the present application is generally low. The impurity element detection data of the iron phosphate prepared by the traditional iron method in Comparative Example 6 shows that the high impurity element content is mainly due to the large phosphorus excess coefficient in the traditional iron method (iron-phosphorus ratio: Fe / P=1 / 2). After most of the Fe elements are precipitated in the system, phosphate precipitates are formed with other impurity cations. The preparation method of the iron phosphate material provided in Examples 1-11 of the present application controls the iron-phosphorus ratio to be 1:(1~1.2). After the iron phosphate is precipitated, there are fewer free phosphates, and impurity cations are not easy to form phosphate precipitates.

[0254] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. An iron phosphate material, characterized in that: The iron phosphate material includes iron phosphate particles, the iron phosphate particles have a ring structure, and the D50 particle size of the iron phosphate particles is less than 1 μm.

2. The iron phosphate material according to claim 1, characterized in that The aggregation index of the particle size of the iron phosphate particles satisfies: 0.5≤(D90-D10) / D50≤2.

3. The iron phosphate material according to claim 1, characterized in that: The ratio of the average inner diameter to the average outer diameter of the annular structure of the iron phosphate particles is (0.35-0.48):1; The average inner diameter of the ring structure of the iron phosphate particles ranges from 178 nm to 559 nm, and the average outer diameter of the ring structure of the iron phosphate particles ranges from 474.60 nm to 1188.90 nm.

4. The iron phosphate material according to any one of claims 1 to 3, characterized in that The specific surface area of ​​the iron phosphate particles is 13 m 2 / g~20m 2 / g.

5. A method for preparing an iron phosphate material, characterized in that: The steps include: preparing an iron-phosphorus solution comprising a ferrous ion source, a chloride ion source, and a phosphate ion source, wherein the pH value of the iron-phosphorus solution is not greater than 1.5; The iron-phosphorus solution is heated to above 70° C., and then an oxidant is added to the iron-phosphorus solution to obtain an iron phosphate slurry; The ferric phosphate slurry is heated to boiling, and after the ferric phosphate slurry changes color, the boiling state is maintained for 1.5 hours to 4 hours to obtain a first slurry; Mixing the first slurry with low-temperature dilution water to obtain a second slurry; The second slurry is subjected to solid-liquid separation to obtain an iron phosphate material.

6. The method for preparing the iron phosphate material according to claim 5, characterized in that: The molar ratio of the iron element, the phosphorus element and the chlorine element in the iron-phosphorus solution is (0.8-1.2): (0.8-2): (0.5-3); The oxidant is selected from an aqueous solution of hydrogen peroxide, the molar ratio of hydrogen peroxide in the aqueous solution of hydrogen peroxide to the iron element in the iron-phosphorus solution is (0.6-1):1, and the concentration of the iron element in the iron-phosphorus solution is 0.5 mol / L-2.0 mol / L; The mass fraction of hydrogen peroxide in the aqueous solution of hydrogen peroxide is 20% to 30%; The ferrous ion source is selected from one or both of ferrous nitrate and ferrous chloride; The chloride ion source is selected from at least one of hydrochloric acid and ferrous chloride; The phosphate ion source is selected from at least one of H3PO4, (NH4)H2PO4, and (NH4)2HPO4.

7. The method for preparing the iron phosphate material according to claim 6, characterized in that: The preparation steps of the iron-phosphorus solution are as follows: Heat the dilute hydrochloric acid aqueous solution to 50°C to 70°C, then add the elemental iron material to react to obtain a ferrous chloride solution, wherein the concentration of the dilute hydrochloric acid aqueous solution is 1.0 mol / L to 4.0 mol / L; Adding phosphoric acid and water to the ferrous chloride solution, mixing and controlling the pH value to be no greater than 1.5, to obtain the iron-phosphorus solution; The steps of heating the iron-phosphorus solution to above 70° C. and then adding an oxidant to the iron-phosphorus solution to obtain an iron phosphate slurry include: The iron-phosphorus solution is heated to 70° C. to 80° C., and then an aqueous solution of hydrogen peroxide is added to the iron-phosphorus solution; The step of mixing the first slurry with low-temperature dilution water to obtain a second slurry comprises: The first slurry is mixed with the low-temperature dilution water, and stirred until the mixture changes color to obtain the second slurry; The step of performing solid-liquid separation on the second slurry to obtain the iron phosphate material comprises: The second slurry is subjected to solid-liquid separation, and the obtained solid is washed and dried at 90° C. to obtain the iron phosphate material.

8. The method for preparing the iron phosphate material according to any one of claims 6 to 7, characterized in that: The pH value of the iron-phosphorus solution is 0.2 to 1.5; The temperature difference between the second slurry and the first slurry is not less than 60°C; The mass ratio of the first slurry to the low-temperature dilution water is 1:(10-30).

9. A positive electrode material, characterized in that: The invention comprises at least one of a lithium iron phosphate material and a lithium iron manganese phosphate material, wherein the lithium iron phosphate material is prepared from the iron phosphate material according to any one of claims 1 to 4 or is prepared from the iron phosphate material prepared by the method for preparing the iron phosphate material according to any one of claims 5 to 8, and the lithium iron manganese phosphate material is prepared from the iron phosphate material according to any one of claims 1 to 4 or is prepared from the iron phosphate material prepared by the method for preparing the iron phosphate material according to any one of claims 5 to 8.

10. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode material according to claim 9.

11. A secondary battery comprising a positive electrode, characterized in that: The electrode sheet used for the positive electrode is the positive electrode sheet as described in claim 10.